INTEGRATION OF WEARABLE DEVICES TECHNOLOGY IN HEALTH MONITORING AND CHRONIC DISEASE MANAGEMENT: A LITERATURE REVIEW ON THE DEVELOPMENT OF DIGITAL HEALTH AND ITS IMPACT ON SELF-CARE - Andro Ruben Runtu; Ceril Pungus; Esther Tiarma Hutagaol; Chaterine Diana Pusung; Intan Novita Kowaas (Adisam Publisher, 2026)
This study examines the integration of wearable device technology in health monitoring and chronic disease management through a literature review approach. The results show that this technology is effective in shifting the paradigm from reactive care to predictive healthcare, although it is limited by challenges such as data accuracy, digital fatigue, access disparities, and the need for digital literacy. Therefore, this study recommends a hybrid intervention model based on wearables integrated with local coaching and JKN infrastructure for the Indonesian context, in order to maximise the sustainable transformation of chronic disease management